2018
DOI: 10.3329/bjms.v17i3.37001
|View full text |Cite
|
Sign up to set email alerts
|

Maternal outcome in pregnant women with anaemia

Abstract: Background: Anaemia in pregnancy is one of the most important and common public health problem not only in India but also in most of the South East Asian countries. Anaemia is the most common nutritional deficiency disorder in the world. There is predominance of iron deficiency anaemia (nutritional anaemia). In pregnancy, it is one of the leading causes responsible for maternal morbidity and mortality.Objective: To find out the maternal outcome in pregnant women with anaemia at MMIMSR during the study period w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The characteristics of all 117 included studies are presented in Table S6 (online only, see this Table for Refs. 111–125) . The selected studies were published between 1977 and 2018.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of all 117 included studies are presented in Table S6 (online only, see this Table for Refs. 111–125) . The selected studies were published between 1977 and 2018.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-two of these studies defined anemia using the WHO-conformant threshold of <11 g/dl (Table 1), 9,10,12,14,16,3046 the other 24 studies fell into the Lower or Unspecified Threshold groups and were analyzed separately (Table 2). 11,13,15,4767…”
Section: Resultsmentioning
confidence: 99%
“… Parks et al., 2019 [ 69 ] Retrospective cohort India and Pakistan A total of 92,247 deliveries data was analysed Maternal anaemia was found associated with LBW, stillbirth, preterm birth, neonatal mortality. Singal eta l., 2018 [ 76 ] Case-control study India A total of 400 women given birth were included; 200 of them were anemic Higher occurrence of preterm birth was found among anemic mother. Varsha et al., 2017 [ 79 ] Case-control study India 200 mother-baby were included in this study The occurrence of LBW was found higher among the mothers were anaemic during delivery.…”
Section: Resultsmentioning
confidence: 99%